Hydronephrotic pelvic kidney mimicking urinary retention in an 18-year-old male - Reimold, Philipp; Aksoy, Cem; Tosev, Georgi; Hatiboglu, Gencay; Hohenfellner, Markus (Urology Case Reports, 2022)
We present a case of a hydronephrotic pelvic kidney in an 18-year-old male reporting about inability to void. Ultrasound showed a hypoechogenic mass mimicking a full urinary bladder. Anticipating urinary retention, a foley was inserted but no urin could be aspirated. Imaging showed a hydronephrotic pelvic kidney with no relevant function obstructing the urinary bladder and the contralateral ureter. Nephrectomy was performed and postoperative course was uneventful. A hydronephrotic pelvic kidney is a rare but important differential diagnosis in young men reporting lower abdominal pain and inability to void.